Flue Gas Temperature Distribution as a Function of Air Management in a High-Temperature Biomass Burner - Aleksandra Dzido; Michalina Kurkus-Gruszecka; Marcin Wilczyński; Piotr Krawczyk (Energies)
Nowadays, as a result of the increasing awareness of European societies and new legal regulations, the role of renewable energy sources in individual heating is growing. One of the forms of renewable heat and electricity production is the use of biomass pellet burners coupled with Stirling engines. To ensure high system efficiency, the combustion process of this type of fuel requires an appropriate design of the burners, which can provide high-temperature flue gases. This requirement may be challenging, as the long operation of such a burner may cause the thermal degradation of its components, mainly the upper burner wall. The subject of this analysis was a burner with a nominal power of 10 kW. As the analysis tool, a previously validated CFD model was used. In this work, two ways of thermal degradation prevention are presented. The first one is geometry optimization via secondary air hole distribution. The results show that an appropriate geometrical design of the burner may be an efficient way of shifting the high-temperature zone to the burner axis, which may mitigate the thermal degradation risk. Secondly, the inlet air mass flow is changed to show its impact on the presence and location of the high-temperature zone. Both methods can be treated as interesting ways for solving the challenge of the long-term operation of high-temperature biomass burners by avoiding thermal degradation.